(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
The interpretation of 10 schlumberger vertical sounding (VES) data was carried out at Karji area of Kaduna state, Nigeria. It was an attempt to investigate the variation in the resistivity values of earth materials as it varies with depth within the area. Ohmega Resistivity Terrameter was the principal instrument used. No booster was used as the expected depth is within the range of penetration of the instrument. In this instrument consecutive reading are taken automatically and the result averaged continuously and display. The schlumberger electrode configuration was used in the data acquisition. The field procedure consist of expanding AB (distance between current electrodes) while MN (distance between potential electrodes) is fixed. This process yields a rapidly decreasing potential difference across MN, which eventually exceeded the measuring capacity of the instrument; therefore a larger vale for MN was taken to continue with the survey. The VES curves were interpreted using IP12Win resistivity computer software. The survey area is dominated mainly by four layers, namely; weathered basement, fractured basement and fresh basement. The Topsoil consists of laterites and clay sand with resistivity value of 90-110Î©m from the topsoil to a depth of 10m. The weathered layers constitutes of coarse grain sand with resistivity value of 190-250Î©m at a depth of 10-25m. The fractured layers contains gravels of resistivity value of 500-980Î©m at a depth of 25-44m, while the fresh bedrock is a fresh granitic rock of resistivity value of 1900-4000Î©m.